2017
DOI: 10.48550/arxiv.1712.04045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Choose your path wisely: gradient descent in a Bregman distance framework

Abstract: We propose an extension of a special form of gradient descent -in the literature known as linearised Bregman iteration -to a larger class of non-convex functions. We replace the classical (squared) two norm metric in the gradient descent setting with a generalised Bregman distance, based on a proper, convex and lower semi-continuous function. The algorithm's global convergence is proven for functions that satisfy the Kurdyka-Lojasiewicz property. Examples illustrate that features of different scale are being i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Their main characteristic is that they start with a sparse solution and successively add features to minimize a loss function, this way forming an inverse scale space. As we demonstrate in this article this special feature makes them a well-suited algorithm for NAS, additionally being supported with a rich mathematical theory [23,24,25,26,27].…”
Section: The Methodsmentioning
confidence: 89%
“…Their main characteristic is that they start with a sparse solution and successively add features to minimize a loss function, this way forming an inverse scale space. As we demonstrate in this article this special feature makes them a well-suited algorithm for NAS, additionally being supported with a rich mathematical theory [23,24,25,26,27].…”
Section: The Methodsmentioning
confidence: 89%
“…Bregman Iterations Bregman iterations and in particular linearized Bregman iterations have been introduced and thoroughly analyzed for sparse regularization approaches in imaging and compressed sensing (see, e.g., [37,43,44,45,46,48,49,51]). Linearized Bregman iterations for non-convex problems, which appear in machine learning and imaging applications like blind deblurring, have first been analyzed in [15,16,44]. In [16] it was also shown that linearized Bregman iterations for convex problems can be formulated as forward pass of a neural network.…”
Section: Sparse-to-sparse Trainingmentioning
confidence: 99%
“…In [16] it was also shown that linearized Bregman iterations for convex problems can be formulated as forward pass of a neural network. In [15] they were applied for training neural networks with low-rank weight matrices, using nuclear norm regularization. In [27] a split Bregman approach for training sparse neural networks was suggested and a deterministic convergence result along the lines of [15] is provided in [13].…”
Section: Sparse-to-sparse Trainingmentioning
confidence: 99%
See 2 more Smart Citations